2022
DOI: 10.1093/mnras/stac1869
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric clouds do not impede JWST transit spectroscopy for exoplanets with Earth-like atmospheres

Abstract: The James Webb Space Telescope (JWST) will provide an opportunity to investigate the atmospheres of potentially habitable planets. Aerosols significantly mute molecular features in transit spectra because they prevent light from probing the deeper layers of the atmosphere. Earth occasionally has stratospheric/high tropospheric clouds at 15–20 km that could substantially limit the observable depth of the underlying atmosphere. We use solar occultations of Earth’s atmosphere to create synthetic JWST transit spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
4
0
1
Order By: Relevance
“…Available observations of the planets in the TRAPPIST-1 system have ruled out hydrogen-rich primordial atmospheres for these planets (de Wit et al 2016;Moran et al 2018;Garcia et al 2022), but are unable to break the degeneracy between a cloud-or aerosol-heavy atmosphere, a high molecular mean weight atmosphere, or the absence of an atmosphere, although the JWST may be able to do so in the future (Lustig-Yaeger et al 2019). Some work has offered brighter prospects for the detection of water vapor on arid (icy) planets (Ding & Wordsworth 2022) and found that stratospheric (as opposed to tropospheric) clouds would not necessarily affect observations by the JWST (Doshi et al 2022). As water-rich planets are expected to form substantial cloud decks, this limitation is a significant obstacle to the detection of atmospheric chemistry and potential biosignatures on water-rich habitable worlds.…”
Section: Introductionmentioning
confidence: 99%
“…Available observations of the planets in the TRAPPIST-1 system have ruled out hydrogen-rich primordial atmospheres for these planets (de Wit et al 2016;Moran et al 2018;Garcia et al 2022), but are unable to break the degeneracy between a cloud-or aerosol-heavy atmosphere, a high molecular mean weight atmosphere, or the absence of an atmosphere, although the JWST may be able to do so in the future (Lustig-Yaeger et al 2019). Some work has offered brighter prospects for the detection of water vapor on arid (icy) planets (Ding & Wordsworth 2022) and found that stratospheric (as opposed to tropospheric) clouds would not necessarily affect observations by the JWST (Doshi et al 2022). As water-rich planets are expected to form substantial cloud decks, this limitation is a significant obstacle to the detection of atmospheric chemistry and potential biosignatures on water-rich habitable worlds.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we are able to probe deeper into the Earth's atmosphere than a true Earth-Sun-analog exoplanet observation, where the observer can be assumed to be infinitely far away. While the empirical spectrum from M&C19 and analyzed in this work does not contain cloudy sight lines, we refer readers to the recent work of Doshi et al (2022) for a detailed analysis of the cloudy Earth spectrum derived from the same SCISAT measurements.…”
Section: Observed Datamentioning
confidence: 99%
“…Further exoplanet-analog observations and analyses of Earth and other solar system planets in transit would be beneficial for disentangling these complicated processes (e.g., Mayorga et al 2021). The recent work of Doshi et al (2022) suggests that Earth's clouds are sufficiently low-altitude as to not appreciably impact transmission observations of Earth-like exoplanets transiting M dwarfs; however, 3D GCM models with full atmospheric dynamics do show an impact of higher-altitude clouds in the transmission spectra of similar exoplanets (Komacek et al 2020;, so the general outcome for JWST observations remains uncertain and requires both data and modeling.…”
Section: Model Validation and Limitationsmentioning
confidence: 99%
“…In this model, limb-darkening is not considered. Atmospheric refraction is natively included, but is likely not important for TRAPPIST-1e due to the large angular size of TRAPPIST-1 (Doshi et al 2022). The full 360 transit spectra for each of the 10 cases are shown in Figure 1, along with the time-averaged continuum floor of each case.…”
Section: Spectrum Post-processingmentioning
confidence: 99%